Information Security Risk Measurement Using Information Security Index (KAMI) at the Information Technology and Database Center - Fuadi, Rifqi Syamsul; Tjahjadi, Djajasukma; Astuti, Rini; Setiawan, Dhanny (CoreID Journal, 2023)
UIN Sunan Gunung Djati Bandung, as a rapidly growing higher education institution, faces significant challenges in ensuring information security. This research aims to improve information security at UIN Sunan Gunung Djati Bandung by applying the Information Security Index (KAMI). This method analyzes information security risks to identify potential threats, vulnerabilities, and possible impacts. The analysis revealed that security measures were already in place, but they also highlighted areas that require further attention. By achieving a final score of 415, signifying category II (Basic Framework Fulfillment), this research significantly contributed to understanding information security in higher education. Through the application of WE, this research not only provides a comprehensive overview of the status of information security at UIN Sunan Gunung Djati Bandung but also opens up opportunities to identify and address potential threats more effectively. Thus, the results of this study have important implications for improving information security and protection in higher education institutions and can be a valuable guide for similar institutions in their efforts to mitigate information security risks.